(untitled) (Bangladesh Journal of Bioethics, 2018)
Vaccines are responsible for many global public health successes, such as the eradication of smallpox and significant reductions in other serious infections like diphtheria, pertussis, tetanus, polio and measles. However, mass vaccination has also been the subject of various ethical controversies for decades. Several factors need to be considered before any vaccine is deployed at national programme like the potential burden of disease in the country or region, the duration of the protection conferred, herd immunity in addition to individual protection, vaccine-related risks, financing and the logistical feasibility of the large-scale vaccination. Moreover, several ethical dilemmas revolve around authority and mandates for vaccination, informed consent, benefits vs. risks, and disparities in access to vaccination. This review paper aims to elaborate the ethical issues involved in mass vaccination programme and present some additional challenges in the context of a resource-poor settings of public health in Bangladesh.